2021
DOI: 10.48550/arxiv.2101.08369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The chemical inventory of the planet-hosting disk PDS 70

Stefano Facchini,
Richard Teague,
Jaehan Bae
et al.

Abstract: As host to two accreting planets, PDS 70 provides a unique opportunity to probe the chemical complexity of atmosphere-forming material. We present ALMA Band 6 observations of the PDS 70 disk and report the first chemical inventory of the system. With a spatial resolution of 0. 4 − 0. 5 ( ∼ 50 au), 12 species are detected, including CO isotopologues and formaldehyde, small hydrocarbons, HCN and HCO + isotopologues, and Sbearing molecules. SO and CH 3 OH are not detected. All lines show a large cavity at the cen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…A four-lobed pattern in synthetic integrated intensity maps has been obtained in several radiative transfer calculations with disc inclinations 40 • , like for instance in Liu et al (2018), Keppler et al (2019) and Zhu (2019). This pattern is also clearly discernible in observed integrated intensity maps of the PDS 70 disc, for the 12 CO J=3→2 line (Keppler et al 2019;Facchini et al 2021) and for other molecular lines like HCO + J=4→3 (see Figure 5 in Facchini et al 2021). It is also highly suggestive in the 12 CO, 13 The four-lobed pattern is due to the fact that the gas emission originates from a disc region that has a finite vertical thickness on both sides of the midplane (Rosenfeld et al 2013;Keppler et al 2019).…”
Section: A Four-lobed Pattern At High Optical Depths For Inclined Discsmentioning
confidence: 62%
See 1 more Smart Citation
“…A four-lobed pattern in synthetic integrated intensity maps has been obtained in several radiative transfer calculations with disc inclinations 40 • , like for instance in Liu et al (2018), Keppler et al (2019) and Zhu (2019). This pattern is also clearly discernible in observed integrated intensity maps of the PDS 70 disc, for the 12 CO J=3→2 line (Keppler et al 2019;Facchini et al 2021) and for other molecular lines like HCO + J=4→3 (see Figure 5 in Facchini et al 2021). It is also highly suggestive in the 12 CO, 13 The four-lobed pattern is due to the fact that the gas emission originates from a disc region that has a finite vertical thickness on both sides of the midplane (Rosenfeld et al 2013;Keppler et al 2019).…”
Section: A Four-lobed Pattern At High Optical Depths For Inclined Discsmentioning
confidence: 62%
“…r In the same vein, other molecules need to be explored, especially given the growing chemical inventory in several protoplanetary discs with gas cavities, like AB Aur (Rivière-Marichalar et al 2020) or PDS70 (Facchini et al 2021). Likewise, Regály et al (2010) showed that a planet that is massive enough to pump the eccentricity of its surrounding gas could cause a detectable distortion in the line profile of the CO ro-vibrational fundamental emission at ∼ 4.7 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Even in AB Aur, where SO is detected, an elevated C/O ratio of 1.0 is favoured in the chemical modelling (Rivière-Marichalar et al 2020). Recent observations of the transition disk PDS 70 also report a CS/SO >100 which is in line with a C/O>1 (Facchini et al 2021). This means that the bulk of gas accreted by forming planets in these disks is oxygen poor.…”
Section: Constraints On the C/o Ratio Of The Gasmentioning
confidence: 94%
“…The CS/SO ratio has been proposed as a tracer of the underlying C/O ratio in the gas. Detections of CS and non-detections/tentative detections of SO and SO 2 in many disks (LkCa 15, DM Tau, GO Tau, MWC 480 and PDS 70) indicate a high gas phase C/O ratio around unity in the warm molecular layer (Dutrey et al 2011;Semenov et al 2018;Facchini et al 2021). These observations are directly probing where gas giant planets accrete their atmospheres (Morbidelli et al 2014;Teague et al 2019;Cridland et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of dust (Andrews 2020) and gas (e.g., Pontoppidan et al 2014;Öberg et al 2021;Facchini et al 2021) have revealed much about the overall physical and chemical properties of disks, yet fundamental questions remain unanswered (e.g., Haworth et al 2016;Oberg & Bergin 2020). Studying ices offers a unique and complementary opportunity to probe disk properties, such as their temperature structure and internal radiation field, the sizes of dust grains in various disk regions, the degree to which the molecular inventory is inherited from the protostellar envelope or altered during disk formation, and the amount of vertical and radial mixing of disk material.…”
Section: Introductionmentioning
confidence: 99%